2008
DOI: 10.1353/rhe.2008.0011
|View full text |Cite
|
Sign up to set email alerts
|

Extending Notions of Campus Climate and Diversity to Students' Transition to College

Abstract: This study builds upon previous research on the effect of diversity on college students by examining and modeling the effects of diversity experiences for students of color and White students' transition to college. Specifically, structural equation modeling (SEM) is used to examine the direct and indirect effects of interactions with diverse peers and their sense of belonging in the second year at public universities. Positive interactions with diverse peers result in a greater sense of belonging to the campu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
281
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(318 citation statements)
references
References 49 publications
14
281
2
2
Order By: Relevance
“…The model addresses sense of belonging for college students as a function of the social spaces and contexts of the institution and outlines outcomes related to positive and negative experiences with sense of belonging. Multi-dimensional in nature, a student's sense of belonging is the result of a variety of individual and institutional factors including those related to incoming values and orientations, academic engagement, peer and faculty relationships, and departmental and campus climate (Freeman et al 2007;Johnson et al 2007;Locks et al 2008;Nuñez 2009;Strayhorn 2008). The present study focuses specifically on sense of belonging in the field of computing.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The model addresses sense of belonging for college students as a function of the social spaces and contexts of the institution and outlines outcomes related to positive and negative experiences with sense of belonging. Multi-dimensional in nature, a student's sense of belonging is the result of a variety of individual and institutional factors including those related to incoming values and orientations, academic engagement, peer and faculty relationships, and departmental and campus climate (Freeman et al 2007;Johnson et al 2007;Locks et al 2008;Nuñez 2009;Strayhorn 2008). The present study focuses specifically on sense of belonging in the field of computing.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Minority students who have participated in studies on this topic have cited campus and classroom climate as well as the lack of mentoring as major factors leading to STEM attrition (Hausmann et al 2007;Locks et al 2008). Additional studies have found that students' academic selfefficacy and precollege preparedness both play roles in student success and persistence in STEM disciplines (Braxton et al 2004).…”
Section: Infrastructure and Implementationmentioning
confidence: 99%
“…Student to student interactions and the ability to form positive relationships with a diverse group of peer students is important to the cultural adjustment experience of international students (Locks, Hurtado, Bowman, & Oseguera, 2008). The more positive the interactions an international student has with other students the likelihood the international student will experience a heightened sense of belonging to the campus community.…”
Section: Interactions With the Campus Communitymentioning
confidence: 99%
“…These three groups help form the "campus climate" of the institution, which plays a significant role in the adjustment experiences of students matriculating at the university (Astin, 1993). Campus climate for a newly arrived international student can be determined by how many positive or negative interactions they have with the other members of the community (Locks, Hurtado, Bowman, & Oseguera, 2008) as they get accustomed to their surroundings. The next four themes take a look at the campus climate for the participants in this study, examining the similarities and differences in the adjustment experiences of the students from China and other countries of origin.…”
Section: Domain's Relation To Previousmentioning
confidence: 99%
See 1 more Smart Citation